2022
DOI: 10.1161/atvbaha.121.317166
|View full text |Cite
|
Sign up to set email alerts
|

NAD + Levels Are Augmented in Aortic Tissue of ApoE −/− Mice by Dietary Omega-3 Fatty Acids

Abstract: Background: Maintaining bioenergetic homeostasis provides a means to reduce the risk of cardiovascular events during chronological aging. Nicotinamide adenine dinucleotide (NAD + ) acts as a signaling molecule, and its levels were used to govern several biological pathways, for example, promoting angiogenesis by SIRT1 (sirtuin 1)-mediated inhibition of Notch signaling to rejuvenate capillary density of old-aged mice. NAD + modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…19 Disturbed NAD + homeostasis and decline of intracellular NAD + pool have been widely associated with vascular aging, hypertension, and atherosclerosis. [20][21][22] Serendipitously, our very own study as well as others demonstrate a pivotal role of NAD + repletion in protecting EC from sepsis-induced disease. 23 The role of NAD + in SMC, despite sparsely documented, is suggested to reinstate SMC phenotypic integrity, based on evidence derived from rodent models of aortic aneurysms.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…19 Disturbed NAD + homeostasis and decline of intracellular NAD + pool have been widely associated with vascular aging, hypertension, and atherosclerosis. [20][21][22] Serendipitously, our very own study as well as others demonstrate a pivotal role of NAD + repletion in protecting EC from sepsis-induced disease. 23 The role of NAD + in SMC, despite sparsely documented, is suggested to reinstate SMC phenotypic integrity, based on evidence derived from rodent models of aortic aneurysms.…”
Section: Introductionmentioning
confidence: 77%
“…22 Recent studies have highlighted the importance of the intracellular NAD + pool in maintaining vascular homeostasis. 20,24,42 NAD + deficiency has been linked to EC dysfunction, aortic aneurysm, aortic stiffness, hypertension, and other vascular pathologies. [42][43][44] The underlying mechanism behind NAD + 's role is multifaceted, including notable examples previously implicated in SMC/EC health and pathogenesis of IH, such as NAD + -dependent activation of sirtuin family (SIRTs) and deacetylation of substrate proteins, modulation of oxidative stress response, calcium signaling, and mitochondrial bioenergetics.…”
Section: Discussionmentioning
confidence: 99%
“…Defective NAD+ synthesis contributes to the development of kidney diseases, while maintaining NAD+ bioavailability may mitigate long-term profibrotic pathways leading to CKD (Ralto et al, 2020). Previous studies have shown that n-3 fatty acids may stimulate NAD+ biosynthesis in extrarenal tissues (Chi et al, 2022). Therefore, it is plausible that the high ALA levels in the LR diet could be responsible for attenuating fibrotic changes observed in the SFA and HR groups.…”
Section: Amino Acid Metabolism-related Proteinsmentioning
confidence: 99%
“… 12 Previous studies have shown that n-3 PUFAs significantly inhibited the cellular senescence and tissue aging. 13 , 14 However, the relationship between n-3 PUFAs and senescence of the IVD cells still unknown.…”
Section: Introductionmentioning
confidence: 99%